Implementasi Tari Tradisional pada Anak Sekolah Dasar dengan Menggunakan Metode Fun Learning di Desa Paninggaran - Billa Essa Surya Tiffany Susilawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Kuningan, 2024)
This study aims to implement traditional dance for elementary school children using the fun learning method in Paninggaran Village. The research was motivated by the lack of channeling the potential and talents of children in Paninggaran village in dancing due to the absence of anyone who could practice dance and the absence of a dance studio or special place. The research method uses a qualitative descriptive approach, with descriptive techniques. The process of collecting data in this study is using the method of observation, interviews and documentation. The research subjects were elementary school children in Paninggaran Village. The data analysis technique used is technical triagulation. Based on the results of the study, it showed that the implementation of traditional dance for elementary school children using the fun learning method in Paninggaran village went well and was in line with expectations. Evidenced by the results obtained, namely children who can dance well.